The THE ROLE OF THE GOVERNMENT IN REALIZING THE RIGHT TO WORK AND A DECENT LIVING IN INDUSTRIAL RELATIONS IN INDONESIA - Marbun, Rika Jamin (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The right to work and a decent life is part of human rights as stated in the Indonesian Constitution, namely Article 27 paragraph (2) of the 1945 Constitution. The fulfillment of the right to work and a decent living for Indonesian citizens is the responsibility of the state. The state is obliged to provide employment for every citizen as a means for the community to meet their needs through the work they are engaged in. Likewise, the state is obliged to realize the fulfillment of life needs that are appropriate and appropriate for the community for social welfare. The manifestation of the Government's responsibility is also related to industrial relations, where labor is an important factor in employment relations whose position is often neglected. The method used in this research is normative juridical which examines laws and regulations. As a welfare state, the Indonesian government has a function to carry out national development so that the state is also responsible for protecting and realizing the welfare of all its people. Likewise in industrial relations, the welfare of society, in this case workers, needs to be protected. Primarily through legal instruments, namely Law no. 13 of 2003 concerning Employment in industrial relations facilities. The means of industrial relations serve as a guide in regulating the rights and obligations of the parties in industrial relations. The existence of arrangements on the rights and obligations of the parties is the main key to the realization of harmonious industrial relations. More than that, the ultimate goal is the fulfillment of a decent job and life for every worker/laborer. Keywords: Government, Right to work and a decent living, industrial relations .